A comparison of the quality of image acquisition between the incident dark field and sidestream dark field video-microscopes. Issue 1 (December 2016) - Gilbert-Kawai, Edward; Coppel, Jonny; Bountziouka, Vassiliki; Ince, Can; Martin, Daniel
Abstract Background The 'Cytocam' is a third generation video-microscope, which enables real time visualisation of thein vivo microcirculation. Based upon the principle of incident dark field (IDF) illumination, this hand held computer-controlled device was designed to address the technical limitations of its predecessors, orthogonal polarization spectroscopy and sidestream dark field (SDF) imaging. In this manuscript, we aimed to compare the quality of sublingual microcirculatory image acquisition between the IDF and SDF devices. Methods Using the microcirculatory image quality scoring (MIQS) system, (six categories scored as either 0 = optimal, 1 = acceptable, or 10 = unacceptable), two independent raters compared 30 films acquired using the Cytocam IDF video-microscope, to an equal number obtained with an SDF device. Blinded to the origin of the films, the raters were therefore able to score between 0 and 60 for each film analysed. The scores' distributions between the two techniques were compared. Results The median MIQS (95 % CI) given to the SDF camera was 7 (1.5–12), as compared to 1 (0.5–1.0) for the IDF device (p < 0.0001). Of the six categories assessed by the MIQS, nearly one fifth of the SDF videos were scored as unacceptable for pressure (20 %), content (20 %), and stability (17 %), with focus scoring deficiently 13 % of the time. High agreement between the two raters scoring values was evident, with an intra-class correlation coefficient (ICC) of 0.96 (95 % CI: 0.94, 0.98). Conclusions These results demonstrate that the quality of sublingual microcirculatory image acquisition is superior in the Cytocam IDF video-microscope, as compared to the SDF video-microscope.